MODEL PENYEBARAN PENYAKIT DEMAM BERDARAH DI MALANG - Usman Pagalay (El-QUDWAH, 2007)
A mathematic model plays an important role in the understanding of epidemiology and the spreader of dengue. This model describes briefly about the non-linear process and the infection process of dengue to a person and the emergence of this disease in certain population. An important definition is taken from –this a dynamic analysis, which is focused on the incidence or prevalence of the spreader of a disease in a certain population. It also includes epidemic process in a steady state population. This research explains mathematic models of the spreader of dengue in Malang that covers the number of outbreaks to cope with DBD, the stability of the disease, the endemic area and the prediction of the number of people that are infected by this disease in the future. The dynamic analysis of the host and vector were derived from the formula of differential equation system, and then defined as mathematic model. From this, we can get basic reproduction number (Ra). It is a number that indicate whether a dynamic system from the model is stable.Keyword: Mathematic Model, DBD, epidemic, Outbreak